2022
DOI: 10.3390/antiox11101897
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide Repeat Pathology in C9orf72-ALS Is Associated with Redox, Mitochondrial and NRF2 Pathway Imbalance

Abstract: The hexanucleotide expansion of the C9orf72 gene is found in 40% of familial amyotrophic lateral sclerosis (ALS) patients. This genetic alteration has been connected with impaired management of reactive oxygen species. In this study, we conducted targeted transcriptional profiling in leukocytes from C9orf72 patients and control subjects by examining the mRNA levels of 84 redox-related genes. The expression of ten redox genes was altered in samples from C9orf72 ALS patients compared to healthy controls. Conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…While some studies have reported the Nrf2 pathway to be disrupted in ALS patient samples (60)(61)(62), very limited data exists on C9orf72-related ALS samples. Recently, Jimenez-Villegas et al (63) have shown that Nrf2 activation is impaired in cell culture models of arginine-DPR toxicity, where they also saw an improvement in cell viability upon treatment with DMF. We have extended these findings showing the benefit of targeting Keap1/Nrf2 in vivo as well as patient-derived iNeurons which further emphasises the importance of Nrf2 activation as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported the Nrf2 pathway to be disrupted in ALS patient samples (60)(61)(62), very limited data exists on C9orf72-related ALS samples. Recently, Jimenez-Villegas et al (63) have shown that Nrf2 activation is impaired in cell culture models of arginine-DPR toxicity, where they also saw an improvement in cell viability upon treatment with DMF. We have extended these findings showing the benefit of targeting Keap1/Nrf2 in vivo as well as patient-derived iNeurons which further emphasises the importance of Nrf2 activation as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Onesto et al report an increase in ROS levels in cells expressing mutated C9orf72 altering mitochondrial activity and might be the mechanism behind the cell death observed in ALS (Onesto et al, 2016). Moreover, the expression of redox genes was also observed to be impaired in ALS, where expression of the master regulator of redox genes, i.e., NRF2, is also reported to decrease in cells expressing DPRs (Jimenez-Villegas et al, 2022). On the other hand, the loss of C9orf72 functions is also linked with mitochondrial abnormalities, where C9orf72 controls assembly of complex-I, maintaining OXPHOS.…”
Section: Deciphering the Link Between Amyotrophic Lateral Sclerosis A...mentioning
confidence: 99%
“…However, signs of OS, including protein and lipid peroxidation, were found in non-mutated ALS cases as well [ 131 , 132 , 133 ] and were associated with a decrease in antioxidant enzymes’ activity and with a possible pro-oxidative state [ 134 ].…”
Section: Oxidative Stress and Inflammation In Alsmentioning
confidence: 99%